First, we simplify the expression inside the parentheses:
(5+3) = 8
(6-2) = 4
So now we have:
(1^4⋅8⋅4)2
Next, we simplify the expression inside the first set of parentheses:
Since 1 raised to any power is still 1, the expression becomes:
(1⋅8⋅4)2
Now we simplify the expression inside the second set of parentheses:
8⋅4 = 32
So now we have:
(32)2
Finally, we evaluate the exponent:
32^2 = 32 * 32 = 1024
Therefore, the evaluated expression is 1024.
Evaluate the expression (1^4⋅(5+3)(6−2))2 . Show all your work.(4 points)
1 answer